Baymag - high-purity magnesium oxide from natural magnesite - Hagen B. Schultes (Canadian Institute of Mining, Metallurgy and Petroleum, 1986)
"Refratechnik, a leading German refractory company, acquired a majority shareholding in Baymag in 1979. This acquisition included the mining rights for a magnesite deposit of exceptionally high purity in the Canadian Rocky Mountains.The deposit, situated in the Kootenay region of southeastern British Columbia, is of Cambrian age and has ore reserves of 50 million m. t. of magnesite. The Baymag magnesite deposit is one of the purest in the world. The deposit was opened up and mining commenced in early 1982. Production of various caustic calcined magnesia products in a rotary kiln operation in Exshaw, Alberta, was started in mid-1982. The product application ranges from pulp and paper production, to the chemical industry, and to animal feed supplements. Since the end of 1983, Baymag has produced high-quality refractory grade fused magnesium oxide f or specialty applications in the steel industry.IntroductionAlthough magnesium is the eighth most abundant element in the earth and forms about 2.06% of the earth's crust, common knowledge about magnesium and especially magnesium oxide (MgO) as an industrial mineral is not widespread. The reason might be that, with the exception of magnesium metal as the element, magnesia products are not generally sold as final products to end-users, but rather are needed for the production of final products such as steel, cement, paper, etc. Therefore, some general comments are given about the different sources of MgO, the different products, world production and consumption , before Baymag specifics are addressed. Magnesium metal will not be discussed in this paper."